Improvement of income accounting in monopoly enterprises - Ergasheva Nasiba Rakhmatullaevna; Baibutaeva Farangiz Farhod kizi (THE INNOVATION ECONOMY, 2026)
This article presents scientifically based proposals and recommendations on improving the accounting of income of monopoly enterprises, reducing the cost of products and improving their quality, expanding the theoretical and methodological foundations of ensuring the transparency of information on the formation of financial results of financial and economic activities of monopoly enterprises, developing the theoretical and methodological foundations of the behavior of monopoly enterprises in a competitive market, clarifying the procedure for the formation of income from the activities performed by them, describing the factors affecting it, and improving the accounting of factors based on the structural structure of income, accounting policies and reporting of monopoly enterprises.